Have wind design provisions become too complicated? a look at the progression of design provisions for mid-rise buildings - Morgan, Jessica L. (Kansas State University, 2009)
Wind pressures affect buildings of all shapes and sizes. Standards and codes have been published that instruct engineers and designers how to account for the wind loads interacting with structures. As further research on wind interaction with buildings is completed, more provisions and requirements are added to the codes and standards. At what point do the provision modifications and additions become more complicated than they need to be for a safe, effective building design? This report evaluates the progression of wind provisions through codes and standards since the early 1900’s. Then a detailed review of the current ASCE 7-05 Analytical Procedure design provisions is completed. Specifically, this report focuses on mid-rise structures 60 feet to 180 feet in height, located in the Midwest region of the United States. Following this in depth review of the ASCE 7 Standard, two studies are carried out. The studies were developed in order to assess the following two ideas: Have the wind load provisions become too complicated? Should there be a simplified procedure for mid-rise buildings?
Keywords: Wind loads; Building codes; Standards; Engineering, Civil (0543)